INFLUENCE OF LOCAL FATIGUE DAMAGE ON THE FATIGUE CRACK PROPAGATION RATE - Карускевич, Михайло Віталійович; Корчук, Олена Юріївна; Щепак, Сергій Вікторович (Problems of Friction and Wear, 2019)
Implementation of Damage Tolerance concept requires knowledge of the damages evolution regularities. Before the crack starts propagation the nucleation stage occurs, accompanied by the evolution of some physical and mechanical properties. It was proved early by the set of experiments that deformation relief emerged as a result of cyclical loading can be considered as a quantitative indicator of the accumulated fatigue damage. To the constructional material exhibiting emerging and development of deformation relief could be referred well known aluminium alloys D16AT, V95, 2024T3, 7075T6. The deformation relief on the surface of mentioned materials has been studied by the methods of light microscopy, electron scan microscopy, profilometry, etc. Fatigue crack nucleates at the area of the increased stresses, for example close to the hole for rivet. The moment of a crack emerging is influenced by the different factors mostly accidental. The local fatigue damage at the moment of crack emerging can be different. In this connection the relation of fatigue crack propagation rate and local accumulated damage has been studied. As a quantitative characteristic of the accumulated fatigue damage the parameter of the deformation relief intensity has been used. This parameter is calculated as a ratio of the surface area with signs of micro plastic deformation to the total observed by light microscope area. The area of controlled surface was equal to the area of circle with diameter 0.3 mm. As a result of fatigue tests the close correlation was found between the intensity of deformation relief and fatigue crack propagation rate. This correlation is most strong for the initial stage of fracture, which has the biggest duration. Thus, it can be concluded that the local fatigue damage accumulated at the stage of crack nucleation affects further crack propagation.